2015
DOI: 10.1093/mnras/stv2144
|View full text |Cite
|
Sign up to set email alerts
|

Swiftdetection of the super-swift switch-on of the super-soft phase in nova V745 Sco (2014)

Abstract: V745 Sco is a recurrent nova, with the most recent eruption occurring in February 2014. V745 Sco was first observed by Swift a mere 3.7 hr after the announcement of the optical discovery, with the super-soft X-ray emission being detected around four days later and lasting for only ∼ two days, making it both the fastest follow-up of a nova by Swift and the earliest switch-on of super-soft emission yet detected. Such an early switch-on time suggests a combination of a very high velocity outflow and low ejected m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 69 publications
1
40
4
Order By: Relevance
“…demonstrated a clear difference between the colormagnitude tracks of eruptions from systems hosting a red giant companion (RG-nova) and those having a sub-giant or mainsequence companion (SG-or MS-nova). The color-magnitude track evolves almost vertically along the line of -= B V 0 ( ) -0.03 (the intrinsic color of optically thick free-free emission; as shown in Figure 7, along with -= B V 0.13 0 ( ) for optically thin free-free emission; also see the discussion in Section 7.2) for RNe harboring a red giant companion, such as V745Sco (2014 eruption, data from Page et al 2015; also see Section 7.6) and RS Oph (1958Oph ( , 1985Oph ( , and 2006 ), respectively. On the other hand, the track goes blueward and then turns back redward near the two-headed arrow, as shown in Figure 7(c), for RNe with a sub-giant or main-sequence companion-for example, USco, CIAquilae, and TPyxidis (data from Pagnotta et al 2015, VSOLJ, and AAVSO/SMARTS, respectively).…”
Section: Color-magnitude Evolutionmentioning
confidence: 85%
See 3 more Smart Citations
“…demonstrated a clear difference between the colormagnitude tracks of eruptions from systems hosting a red giant companion (RG-nova) and those having a sub-giant or mainsequence companion (SG-or MS-nova). The color-magnitude track evolves almost vertically along the line of -= B V 0 ( ) -0.03 (the intrinsic color of optically thick free-free emission; as shown in Figure 7, along with -= B V 0.13 0 ( ) for optically thin free-free emission; also see the discussion in Section 7.2) for RNe harboring a red giant companion, such as V745Sco (2014 eruption, data from Page et al 2015; also see Section 7.6) and RS Oph (1958Oph ( , 1985Oph ( , and 2006 ), respectively. On the other hand, the track goes blueward and then turns back redward near the two-headed arrow, as shown in Figure 7(c), for RNe with a sub-giant or main-sequence companion-for example, USco, CIAquilae, and TPyxidis (data from Pagnotta et al 2015, VSOLJ, and AAVSO/SMARTS, respectively).…”
Section: Color-magnitude Evolutionmentioning
confidence: 85%
“…Additionally, while for M31N 2008-12a we speculate, in Section 7.4, that the short recurrence time may require the accretion disk to stay intact, it may not survive the eruption in V745Sco, thus delaying the next eruption by at least the time it takes for accretion to resume again. Page et al (2015) reported that V745Sco showed no variability during the early SSS phase. However, the observed smooth rise to peak flux was exceptionally rapid and was essentially covered by only six observations, which might not have been sufficient to capture variability.…”
Section: Comparison To V745 Scorpiimentioning
confidence: 99%
See 2 more Smart Citations
“…Observations of recurrent novae have shown that they evolve much faster than typical classical novae, which is demonstrated by their very short X-ray turn-on time (duration between the optical peak to the X-ray turn-on, see, e.g., Page et al 2015, for the shortest 4 day case of V745 Sco). By analogy, and without observational support, we suspect that the rising phase of recurrent novae must also be fast.…”
Section: Slow Evolution After X-ray Flashmentioning
confidence: 99%